Evaluation of Charge Transfer Blocks in CP Circuit Topologies - Mohd Kamel, Mohamad Khairul; Wong, Yan Chiew (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Harvested energy major challenge in self-powered devices is due to its low power energy supply. Therefore, a charge pump is required to overcome this constraint. Charge pumps are inductorless DC-DC converters that have the ability to transfer charge to the high level through the effectiveness of switches to turn on and off at the designated clock phases. This paper investigates the features of charge transfer switches in two and four-phase charge pump. The charge pumps have been evaluated in terms of the output voltage and leakage current in charge transfer block. The sizing of transistor, frequency, stage and load capacitance have been optimized. The rise time has been analysed over the stage and load capacitance. The correlation on the performance of charge pump has been observed. The charge pumps have been simulated in 130nm standard CMOS process.